An investigation into the effect of manifold geometry on uniformity of temperature distribution in a PEMFC stack. (15th February 2018) - Amirfazli, Amir; Asghari, Saeed; Sarraf, Mohammad
Abstract: Thermal management is one of the most significant issues in reliability and durability enhancement of proton exchange membrane fuel cell (PEMFC). In this study, an experimentally validated analytical-numerical model of the stack is used to investigate the effect of manifold and cooling flow field channel dimensions on stack temperature uniformity. Moreover, a concept design for cooling manifold has been introduced with the purpose of increasing the total active area of the stack as well as achieving a more uniform distribution of the coolant flow rate between the cells. The U and Z stack configurations with various manifold cross sectional area and cooling flow field channel dimensions are compared with each other. The results indicate that decreasing the flow field channel dimension increase the stack temperature uniformity while increasing the manifold cross sectional area does not essentially increase the stack temperature uniformity. The introduced concept can be a feasible design for the limiting space application of fuel cell since more active area can be achieved with the same stack dimensions and temperature uniformity. However, the direction of the flow (stack configuration) would be the key issue to be considered in selection of the incremental direction of the manifold cross sectional area. Highlights: Effect of manifold geometry on stack temperature uniformity is investigated. A concept of stack with variable cooling manifold dimensions is introduced. Variable manifold leads to more uniform temperature distribution in a PEMFC stack. Increasing area in Z-type stack doesn't essentially increase temperature uniformity. Contrary to U-shape, the inlet-outlet manifolds areas in Z-shape affect each other.